Effects of Music Therapy and Inhalation Aromatherapy on Pain Intensity, Anxiety, and Fear Levels in Patients Undergoing Coronary Angiography: A Randomized Controlled Trial - Gur, Fatma; Turan, Gulcan Bahcecioglu (Wiley, 2026)
Objective: To examine the effects of music therapy, inhalation aromatherapy, and their combination on pain intensity, anxiety, and fear in patients undergoing coronary angiography. Methods: This randomized controlled trial included 128 patients assigned to four groups: control, music therapy, aromatherapy, and combined music + aromatherapy. Interventions were applied 5-10 min before the procedure and continued during angiography. Visual analog scales for assessing pain (VAS-P), anxiety (VAS-A), and fear (VAS-F), and the State Anxiety Inventory (SAI) were assessed pre- and postprocedure. Data were analyzed using mixed-design ANOVA to examine time, group, and time & times; group effects, and effect sizes (eta(2)) were calculated. Results: Significant time & times; group interactions were found for pain (eta(2) = 0.205), fear (eta(2) = 0.527), anxiety (eta(2) = 0.550), and state anxiety (eta(2) = 0.546) (all p < 0.001). All intervention groups showed greater reductions in pain, anxiety, and fear compared with the control group (p < 0.001). No significant differences were observed among the three intervention groups (p > 0.05), although the combined intervention yielded the largest improvements. Conclusion: Music therapy and inhalation aromatherapy reduce pain, anxiety, and fear in patients undergoing coronary angiography effectively and can be recommended as nonpharmacological nursing interventions.
Keywords: anxiety; aromatherapy; coronary angiography; music therapy; pain